Host plant specificity of corticolous lichens in urban and suburban New Amsterdam, Berbice, Guyana - Bebe Raazia Bacchus; Phillip N.B. Da Silva (GSC Biological and Pharmaceutical Sciences, 2021)
In this study, host plant - lichen specificity was investigated. Data was collected from 1000m2 sampling plots at each of four locations with an established 50m x 20m plot at each site. Forty-one trees from across five species were examined using (10cm by 50cm) ladder quadrats on tree trunks (N, S, E, W) at 150cm height. A total of 14978 individual lichens were identified that yielded 10 families, 13 genera and 18 species. Swietenia mahagoni showed the highest average corticolous lichen species composition, followed by Terminalia catappa and Melicoccus bijugales respectively. Cocos nucifera had a higher average species recorded than Mangifera indica. Crustose lichens were the most prominent corticolous lichens observed (61%) with the most individuals in Graphidaceae and Arthoniaceae. Foliose lichens (28%) showed the most abundance in Parmeliaceae, Caliciaceae and Collemataceae. Of the taxa recorded, 22.2% were restricted to specific trees. C. parasitica, H. laevigata, U. cornuta were restricted to S. mahagoni. D. applanata was restricted to C. nucifera. 22.2% of recorded species were found on all of the tree hosts that were examined. Bacidia laurocerasi, Flavoparmelia caperata, Flavoparmelia soredians and Graphina anguina. S. mahagoni hosted 88.9% of all recorded species. Swietenia mahagoni showed the highest average of recorded corticolous lichen species of all host trees with 7.58. Mangifera indica showed the lowest average with 4. The maximum number of species (10) was recorded on one S. mahagoni tree.